Bayesian network technologies applications and graphical models - Mittal, Ankush; Kassim, Ashraf (IGI Publishing, 2007)
"This book provides an excellent, well-balanced collection of areas where Bayesian networks have been successfully applied; it describes the underlying concepts of Bayesian Networks with the help of diverse applications, and theories that prove Bayesian networks valid"--Provided by publisher.